Effect of Different Levels of Zinc Supplementation in Rice Bran Diets on Zinc Status and on The Performance of Laying Hens - Wiranda G. Piliang; Wasmen Manalu (Buletin Ilmu Makanan Ternak, 1988)
The purpose of this experiment were to study the optimal level of zinc in the form of zinc carbonate in the high fiber diet provided by rice bran, and to study the zinc status as well as the performance of laying hens. one control and 9 treatment groups of hisex brown laying hens, 80 in all, were fed diets with 25,50, or 75% rice bran supplemented with 25, 125, or 225 ppm zinc as zinc carbonate.Rice bran diets were isonitrogenous and isocaloric by virtue of varying levels of corn, fish meal, soybean meal and coconut oil. The experiment started at 20 weeks of age and continued 10 months. All rice bran diets produced significantly more income over feed cost than did the cornsoybean meal control. Diets with 25 or 50% rice bran and 125 ppm zinc did not differ significantly from the control in hen-day egg production. Adding 125 ppm zinc to 25 or 50% rice bran gave higher concentration in whole blood and erythrocytes than did addition of 25 ppm. The supplementation of 125 ppm zinc in 25 or 50% rice bran gave the highest zinc availability in the body. The 75% rice bran diet decreased avaibility of added zinc. Data on zinc status were obtained from randomly selected hens given labeled zinc chloride.